THE MOOD STRUCTURE IN NADIN AMIZAHS INSTAGRAM: A SYSTEMIC FUNCTIONAL DISCOURSE ANALYSIS - NANDITA ANDANI, DELYA (LANGUAGE HORIZON, 2019)
This research pinpoints the mood system realized in Nadin Amizah?s Instagram posts, a person behind Instagram account @cakecaine who is also a professional singer and well-known public figure of Indonesia. This study aims at figuring out how language on Instagram is used in Instagram captions by a young famous teenage girl through a point of view of interpersonal metafunction of Halliday?s SFL, specifically, of the Mood System. This Systemic-Functional Discourse Analysis will be employed by qualitative research methods. The findings of this study reveal that in Instagram, the use of mood system is quite various; it covers the declarative mood, interrogative mood, and imperative mood. In regards to the result of this study, it is concluded that in Nadin Amizah?s Instagram, the interaction between speaker and readers occurs in new media communication through captions.